动荡局势下的中国粮食安全分析及应对: 保持冷静, 继续维护贸易畅通; Keep calm and trade on: China's decisive role in agricultural markets under turmoil - Lena Kuhn; Tinoush Jamali Jaghdani; Sören Prehn; Zhanli Sun; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2022)
国际农产品贸易对于维护全球粮食安全起着关键的作用。 一方面， 国际贸易使全球的消费者得以获取多样性的食物（Krivonos 和 Kuhn， 2019）， 另一方面， 贸易也可以通过食品分配机制， 充分利 用各地区气候与资源禀赋的区域差异， 来确保不同地区的人们能 够获得基本的食品保障， 维护全球食品安全（Glauben等， 2022）。 过度强调食品本地化， 并不可取。 虽然本地生产和短食品供应链在 一定程度上可以降低运输成本， 但综合碳排放并不一定降低， 且对 于维护全球和区域的粮食系统的韧性尚存争议（Stein和Santini， 2022）。 当前由于持续的 Covid-19疫情大流行、日益增长的全球粮 食需求和不断频发的极端天气事件， 国际农产品贸易正面临供应 链中断和国际市场价格不断上涨等挑战。 这些挑战均威胁到本已严 峻的粮食安全形势， 尤其是对于那些严重依赖进口的低收入地区。 中美贸易战和俄乌冲突等地缘政治风险更是雪上加霜， 进一步扰乱 了全球粮食市场。 在此动荡时期， 作为世界上最大的农产品消费国 和进口国， 中国的贸易战略和行为必然影响着国际市场， 对世界各 地的消费者， 特别是在全球南方发展中国家(Global South)， 可能会 产生连锁反应。 本政策简报旨在分析中国当前的市场行为， 以及可 能采取的中短期行动及其影响。 我们主张中国及相关国家都应采取 稳健和冷静的行动应对短期冲击， 应避免过度流动限制和增加贸易 壁垒以及过度囤积行为， 共同维护正常的国际食品贸易， 以应对人 口增长和气候变化带来的长期的、严峻的全球挑战。 – – International agricultural trade is key to improving global food security. It ensures access to more diversified foods (e.g. Krivonos and Kuhn 2019 ), acts as a safety net against local production shortfalls (Glauben et al. 2022) and helps make use of regional climatic or resource-related production advantages. While local production and short supply chains can reduce transport costs, they do not necessarily equate to resilient food systems or lower carbon footprints (Stein and Santini 2022). Currently, though, international agricultural trade is facing supply chain disruptions and rising world market prices resulting from the ongoing Covid-19 pandemic, increasing global food demand and extreme weather events. Both are threatening already strained food security, in particular in import-dependent, low-income regions. Geopolitical risks, such as the China-US trade war and Russia's invasion of Ukraine, are further rattling the food market. As the world's largest consumer of agricultural goods, China's trade strategies influence world markets, with ripple-down effects for consumers around the world, particularly in the Global South. This policy brief aims at shedding light on China's current market actions, and the likely short- and mid-term developments and their impacts. We argue for moderation in response to short-term shocks. Excessive mobility and trade restrictions as well as extreme stockpiling should be avoided. These harm the trade system's overall capacity to resist further and more serious global challenges related to population growth and climate change.
urn:nbn:de:gbv:3:2-997753
Keywords: Q17; Q11; Q18; 330; food security; foreign agricultural trade; agricultural market; import; food price; China; Agraraußenhandel; Import; China; Agrarmarkt; Lebensmittelpreis; Welt